Possible Role of Extracellular Nucleotides in Ectopic Ossification of Human Spinal Ligaments - Toshitada Sawada; Masaki Kishiya; Kouta Kanemaru; Kazuhiko Seya; Toru Yokoyama; Kazumasa Ueyama; Shigeru Motomura; Satoshi Toh; Ken-Ichi Furukawa (Elsevier, 2008)
To reveal the involvement of extracellular nucleotides in the ossification process in ossification of the posterior longitudinal ligament of the spine (OPLL), the mRNA expression profiles of P2 purinoceptors, mechanical stress-induced ATP release, and ATP-stimulated expression of osteogenic genes were analyzed in ligament cells derived from the spinal ligament of OPLL patients (OPLL cells) and non-OPLL cells derived from the spinal ligaments of cervical spondylotic myelopathy patients as a control. The extracellular ATP concentrations of OPLL cells in static culture were significantly higher than those of non-OPLL cells, and this difference was diminished in the presence of ARL67156, an ecto-nuclease inhibitor. Cyclic stretch markedly increased the extracellular ATP concentrations of both cell types to almost the same level. P2Y1 purinoceptor subtypes were intensively expressed in OPLL cells, but only weakly expressed in non-OPLL cells. Not only ATP addition but also cyclic stretch raised the mRNA levels of alkaline phosphatase and osteopontin in OPLL cells, which were blocked by MRS2179, a selective P2Y1 antagonist. These increases in the expression of osteogenic genes were not observed in non-OPLL cells. These results suggest an important role of P2Y1 and extracellular ATP in the progression of OPLL stimulated by mechanical stress. Keywords:: ligament cell, ectopic ossification, P2 purinoceptor, ATP, mechanical stress